The Effectiveness of the Jigsaw Learning Model in Improving Students’ Learning Outcomes in Carbon Chemistry - Wijayanti, Theresia Ita; Field, Steven J; Rashedy, Khawla (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to examine the effectiveness of the Jigsaw cooperative learning model in improving students’ learning outcomes and learning motivation in carbon chemistry at the secondary school level through a classroom-based instructional intervention. Methodology: This study employed classroom action research with three instructional cycles. The Jigsaw cooperative learning model was implemented using lesson plans and student worksheets. Data were collected through achievement tests, observation sheets, motivation questionnaires, and attitude questionnaires. Descriptive quantitative analysis was conducted using Microsoft Excel. Main Findings: The results show a consistent improvement in students’ learning outcomes across three cycles, indicated by increased average scores, mastery levels, and absorption rates. Students’ affective aspects and learning motivation also improved, with most students reaching moderate to high motivation levels and showing more positive attitudes toward chemistry learning. Novelty/Originality of this study: This study provides new empirical evidence on the integrated impact of the Jigsaw learning model on cognitive, affective, and motivational aspects in carbon chemistry. Unlike previous studies focusing mainly on achievement, this research highlights how structured peer collaboration enhances conceptual understanding and learning motivation in abstract chemistry topics.